Bismuth-antimony as an alternative material for high temperature lead-free solder - Muhamad Zam, Shahrul Fadzli (2012)
The development works on high temperature lead free solder are mostly discussed nowadays. To replace the current high temperature lead free solders it would be the great problem. To become a viable high temperature lead free solder alternative for electronics assembly use, it is considered essential for this candidate solder to meet the following criteria such as melting temperature in the range of 260°C to 400°C, small volume expansion at reflow treatment that does not break a package and narrow plastic range. Recent example of high temperature lead free solders are Sn-Sb, Au-Sn, Bi-Ag, Cu-Sn and Zn-Al. Apparently, none of alloys investigated can meet and fulfill all the lead free solder criteria. Virtually all of the lead-free solder alternatives explored so far utilize tin as one of the primary constituent. A great deal of effort has been put into the development lead free solder alloys and Bi (Bismuth) and Sb (Antimony) solder system is proven to be one of the promising candidates for electronic assembly. Through this research, 95Bi-5Sb, 97.5Bi-2.5Sb and 98.5Bi- 1.5 solder alloys were firstly tested by DSC and results showed potentially to be high temperature lead free solder in terms of melting temperature. Each solder alloy soldered to Cu substrate through as reflow, second reflow and third reflow soldering. Interfacial reaction between solder alloys and Cu substrate has been characterized in terms of interfacial microstructure formed at interface and in solder bulk. Cu3Sb intermetallic (IMC) layer precipitated at interface and floating in solder bulk only for 95Bi-5Sb solder alloy through all types of reflow. Cu3Sb IMC layer decreased after reflow. However, no IMC layer precipitated for 97.5Bi-2.5Sb and 98.5Bi-1.5Sb solder alloy. From characterization, it found that only mechanical grain boundary grooving, Cu rich phase and Bi-Cu rich phase formed during different types of reflow for these solder alloys. As conclusion, the developed solder seems to have capability for high temperature lead free solder.